Doctors Dealing With COVID-19 in Pakistan: Experiences, Perceptions, Fear, and Responsibility - Ali, Inayat; Sadique, Salma; Ali, Shahbaz (Frontiers in Public Health, 2021)
This study aimed to describe the dealings of 20 biomedical doctors with coronavirus disease-19 (COVID-19) in the Sindh province of Pakistan. Focusing on physicians from three different hospitals, we describe their challenges, emotions, and views concerning the pandemic. Many regarded the virus from a biomedical standpoint. Yet some also perceived it as a “tool of a proxy war” and a “plot,” without giving agency to anyone for that “plot.” Furthermore, these care providers faced a great fear of infection and an even greater fear of transmitting the virus to their families and friends. A few also feared stigmatization as viral carriers. Whether they experienced fear or not, all of our physician interlocutors emphasized their sense of responsibility to “serve humanity,” yet some also expressed a strong belief in the inevitability of the will of Allah. Some were satisfied with the role of the government in containing the virus, while others expressed concerns and felt that the government should be doing much more. All expressed confidence in the use of personal protective equipment (PPE), viewing it as an effective buffer against viral contagion. We conclude with a call for further research especially ethnographic studies on dealings of physicians with COVID-19 across Pakistan as frontline care providers.